Rasionalitas Kisaran Harga Pupuk Urea dan NPK pada Usaha Tani Padi - Sumaryanto; Susilowati, Sri Hery (Analisis Kebijakan Pertanian, 2023)
In determining the price of subsidized Urea and NPK fertilizers, the Government faces a dilemma. If it is not increased, the gap with market prices will widen, thereby reducing the effectiveness of its distribution and marketing policies. In addition, the wide gap between subsidized fertilizer and market prices is inconsistent with sound fiscal policy and is not conducive to increasing farming efficiency. Conversely, if it is increased, it will negatively impact rice production and farmers’ income in the short term. To minimize this negative impact, the price of subsidized fertilizer must be based on the convergence between efforts to increase efficiency and farmers’ aspirations. In perfectly competitive market conditions, a quantitative measure that reflects the aspirations of farmers can be proxied from the range of the ratio of fertilizer prices to output prices which is equivalent to their marginal productivity. This study aims to determine the range of price ratios of Urea and NPK fertilizers to the price of rice at the farmer level, which is rational for determining subsidized fertilizer prices. The data used are the results of rice farming surveys in 2010, 2013, 2016, and 2021 with a total sample of 2,255 farming units in rice production centers in 18 provinces. The analytical method uses the Stochastic Production Frontier approach to estimate technical efficiency and the Linear Production Function model to estimate the marginal productivity of Urea and NPK. Furthermore, the marginal productivity value is used to determine the ratio range of Urea and NPK prices to the price of harvested dry grain. The study results show that based on the value of marginal productivity, the price range for Urea and NPK fertilizers is quite wide, with market prices in between. Consequently, the price ratio range for NPK fertilizer is wider than for Urea fertilizer.